Application of Coffee Pulper and Huller Machines Technology in Salak District in Improving Coffee Post-Harvest Efficiency and Effectiveness - Karina Nola Sinamo; Putri Chandra Ayu; Sentosa Ginting; Edy Syahputra Harahap (Talenta Publisher, 2025)
Robusta coffee is one of the superior agricultural varieties in Salak District, Pakpak Bharat Regency because it has a strong aroma and a more bitter taste. Partner of one of the robusta coffee farmers in Salak District still use traditional tools to peel the coffee cherries they cultivate. This is an obstacle in the post-harvest processing of coffee. This coffee fruit peeling tool requires a lot of manpower, a long time, and a large percentage of unpeeled coffee cherries. Therefore, the community service team helped overcome the partner's problem with the aim of implementing post-harvest technology in coffee bean production. The method used was the provision of pulper and huller machines and practical training in using these machines in the application of post-harvest coffee processing. The results obtained were that almost 100% of the coffee fruit skin and coffee horn skin were peeled using the pulper and huller machines. The percentage of coffee beans produced by the pulper machine is 64-74% of wet coffee cherries and the percentage of dry coffee beans without horn skin produced by the huller machine is 38,18-42,19% of peeled coffee beans with pulper machine.